O Mercosul ante os mega-acordos regionais - Carvalho, Marina Amaral Egydio de,Salles, Marcus Maurer de (Instituto de Pesquisa Econômica Aplicada, 2024)
This Discussion Paper identifies the rules on public procurement provided for in the Comprehensive and Progressive Agreement for Trans-Pacific Partnership (CPTPP), the Regional Comprehensive Economic Partnership (RCEP) and the African Continental Free Trade Area (AfCFTA). Furthermore, the work compares the rules provided for in these mega-agreements with the rules on public procurement available in the agreements signed by Mercosur internally and with its external partners, as well as relating these rules to those provided for by the World Trade Organization (WTO).
10.38116/td3006-port
Keywords: Graue Literatur; income distribution; computable general equilibrium models; carbon pricing